School Children Attitude Towards School Modernization and Their Role in It - Gumuliauskienė, Aušrinė (Acta Paedagogica Vilnensia, 2002)
Need in Lithuanian school modernization induces scientists to learn about the pupils' conception of modern school vision and mission, their attitude towards the school changes and related problems. Data of investigation shows that pupils do not understand the modern school conception and their role in the course of modernization, personal and school activity changes enough, therefore they with difficulty forecast the direction and character of the school activity. Pupils' concept of a modem school most of all is related with the material supply of the school, making relations between the teachers and pupils more democratic, arrangement of more efficient after - school activity. Pupils have no initiative in the creative search for modem school. They say the following are the most important subjective obstacles of the school change: conservative teachers, insufficient competence, and lack of initiative, incompatible attitudes. Pupils cannot easily imagine directions and character of improvement of themselves.
Keywords: School; modernization; modern school conception; school vision; school mission.